Japanese educational aid in transition: between the aid coordination and unique model. Issue 1 (20th December 2013) - Yamada, Shoko
Abstract : Purpose: – The purpose of this paper is to untangle the domestic and international factors that have affected policy making and implementation of the Japanese Overseas Development Assistance (ODA), particularly in education, at different times in its history. Design/methodology/approach: – The study is based on analysis of governmental policy documents and reports, minutes of ODA consultative meetings, and statistical data on Japanese financial and technical developmental assistance. The major methodology was discourse analysis of primary documents; secondary sources supplement this. Findings: – Japan was the first non-western Organisation for Economic Co-operation and Development-Development Assistance Committee (OECD-DAC) member and has always been in the ambivalent position of being both a DAC member and an Asian latecomer. As the Education for All paradigm took the ground, Japanese ODA to the education sector has shifted to the primary education from Technical and Vocational Education and Training and higher education from the mid-1990s until the mid-2000s. While the global trend is clear in Japanese ODA, it has always stressed the importance of establishing and demonstrating the "Japanese model" in ODA policy documents and practices. The sensitive balance between the demand to harmonize with mainstream aid modalities and the drive to demonstrate uniqueness characterize Japanese educational aid. Originality/value: – While many important works examined the decision-making mechanism and philosophies of Japanese educational ODA, this paper contextualizes governmental programs in the intersection between domestic factors – bureaucratic, political, and societal – and international influence. It clarifies the changing relationships between Japan and western and Asian countries in determining its agendas and directions from the 1960s to the present.